PENERAPAN ARSITEKTUR KONTEMPORER PADA PERANCANGAN BOGOR CREATIVE CENTER DI KOTA BOGOR, JAWA BARAT - Sidiq, Muhammad Fahmi; Sulistiowati, Anggraeni Dyah; Subagya, Karya (MAESTRO, 2021)
Bogor city is a city in the province of West Java, Indonesia, which includes a city with a high density with a population of 1,048,610 people. As a metropolitan area (Jabodetabek), aspects of life that develop in the city of Bogor are very diverse. One of the aspects that developed in the city of Bogor is the economic sector of the community. The economic sector is one of them is the creative industry. In accordance with the vision of the Bogor city government that wants to realize a healthy, intelligent, and prosperous Bogor city with one of the flagship programs of service development and creative economy, as well as the Regional Government of West Java province which is also committed to continue to develop the creative economy (ekraf). Therefore, Bogor Creative Center is also expected to be a place to learn and accommodate the creative industry community until something produced gets a high selling value, as well as in accordance with the needs in architectural rules. The construction of Bogor Creative Center with the concept of contemporary architecture can reflect the freedom of work so that it displays something different and is a new tradition or merger of several other architectural styles.